Relationship between pedagogical competence and teacher performance in public elementary school - Novebri Novebri; Kasman Rukun; Ahmad Sabandi (International Conferences on Educational, Social Sciences and Technology)
This research was based on a case where the result of observation by researcher in Public Elementary School, that showed the low level of teacher performance. Many factors affected the teacher performance which is pedagogical competence. The purpose of this research is to know about the relationship of pedagogical competence to teacher performance in Public Elementary School. The method of this research was quantitative research with 78 teachers. Instrument in this research used teacher competence test. The results of the analysis data showed that pedagogical competence contributes significantly to teacher performance in Public Elementary School of 21.9 % and 78.1% of remaining influenced by another factors. The recommendation in this research is the teachers may improve pedagogical competence and teacher performance.